Reproductive Organ and Vascular Specific Promoter of the Rice Plasma Membrane Ca(2+)ATPase Mediates Environmental Stress Responses in Plants - Huda, Kazi Md. Kamrul (Public Library of Science, 2013)
BACKGROUND: Plasma membrane Ca(2+)ATPase is a transport protein in the plasma membrane of cells and helps in removal of calcium (Ca(2+)) from the cell, hence regulating Ca(2+) level within cells. Though plant Ca(2+)ATPases have been shown to be involved in plant stress responses but their promoter regions have not been well studied. RESULTS: The 1478 bp promoter sequence of rice plasma membrane Ca(2+)ATPase contains cis-acting elements responsive to stresses and plant hormones. To identify the functional region, serial deletions of the promoter were fused with the GUS sequence and four constructs were obtained. These were differentially activated under NaCl, PEG cold, methyl viologen, abscisic acid and methyl jasmonate treatments. We demonstrated that the rice plasma membrane Ca(2+)ATPase promoter is responsible for vascular-specific and multiple stress-inducible gene expression. Only full-length promoter showed specific GUS expression under stress conditions in floral parts. High GUS activity was observed in roots with all the promoter constructs. The −1478 to −886 bp flanking region responded well upon treatment with salt and drought. Only the full-length promoter presented cold-induced GUS expression in leaves, while in shoots slight expression was observed for −1210 and −886 bp flanking region. The −1210 bp deletion significantly responded to exogenous methyl viologen and abscisic acid induction. The −1210 and −886 bp flanking region resulted in increased GUS activity in leaves under methyl jasmonate treatments, whereas in shoots the −886 bp and −519 bp deletion gave higher expression. Salicylic acid failed to induce GUS activities in leaves for all the constructs. CONCLUSIONS: The rice plasma membrane Ca(2+)ATPase promoter is a reproductive organ-specific as well as vascular-specific. This promoter contains drought, salt, cold, methyl viologen, abscisic acid and methyl jasmonate related cis-elements, which regulated gene expression. Overall, the tissue-specificity and inducible nature of this promoter could grant wide applicability in plant biotechnology.